2018
DOI: 10.1002/pc.24977
|View full text |Cite
|
Sign up to set email alerts
|

Optical and dielectric properties of PMMA (poly(methyl methacrylate))/carbon dots composites

Abstract: The optical and the dielectric properties of an original nanocomposite based on the incorporation of carbon dots (C‐dots) in poly(methyl methacrylate) (PMMA) at several filler loading were studied. The optical characterization demonstrated the preservation of the excitation dependent intense emission of the C‐dots in the polymer, ascribed to the presence of organic fluorophores formed during the nanoparticle synthesis. The composite PMMA/C‐dots dielectric properties were investigated in the frequency range fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 36 publications
1
16
0
1
Order By: Relevance
“…As reported in our previous works, upon the incorporation in PMMA matrix the morphological and optical properties of C‐dots remain unchanged, sincenanoparticles appear to retain their size and shape in the nanocomposites blend and preserve their characteristic optical properties, both in solution and in freestanding films.…”
Section: Methodssupporting
confidence: 72%
See 2 more Smart Citations
“…As reported in our previous works, upon the incorporation in PMMA matrix the morphological and optical properties of C‐dots remain unchanged, sincenanoparticles appear to retain their size and shape in the nanocomposites blend and preserve their characteristic optical properties, both in solution and in freestanding films.…”
Section: Methodssupporting
confidence: 72%
“…Previous work reported that the results of an analysis of experimental data to extract information about the dielectric relaxation and the electric modulus of PMMA/C‐Dots nanocomposites . This study showed that the electric modulus formalism was capable of revealing the interfacial relaxation, which, in most cases, is covered by the conductivity of the material when represented in the dielectric permittivity mode.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Remarkably, such an improvement enables a fast synthesis of CDs, confirming the viability of such a unique synthetic strategy for producing CDs in a fast, reproducible, cost-effective and sustainable way. Finally, the dispersion in organic solvents allows the incorporation of the CDs into host polymers for nanocomposite preparation, and their fabrication as thin film [ 58 , 59 ] or further micromachining, thanks to the convenient film-forming properties of suitable organic solvents and their compatibility with clean room manufacturing. Such advanced processability paves the way for an effective integration of the luminescent CDs into photonic devices, LEDs or sensors [ 56 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The size of C‐dots can vary from few nm to tens of nanometers, and be doped with several elements such as N, S, P, and B in imparting new functional properties 30 . C‐dots also have exceptional properties, as they are biocompatible, high aqueous solubility, and great photoluminescence properties 30,31 . Moreover, the fabrication of C‐dots is facile and economical with intrinsic favorable characteristics in many applications including drug delivery, photocatalyst, antibacterial material, biosensor, and bioimaging 30–32 .…”
Section: Introductionmentioning
confidence: 99%